Carta de Roberto H. Todd a Antonio R. Barceló - Todd, Antonio R.; Barceló, Antonio R. (My University, 1931)
Actitud del Auditor Municipal en el pleito del Municipio de San Juan.
Keywords: Barceló, Antonio R., 1868-1938; Gobierno Municipal--Puerto Rico.; Municipal government--Puerto Rico.